Brief history of the recognition of phraseology in cultural linguistics aspect. (Journal of Oriental Studies, 2016)
This article describes the history of the recognition of phraseology in lingvokulturologicheskom aspect of foreign and domestic researchers.
Keywords: phraseology; cultural linguistics; linguistics; culture; language